U.S. Air Force strategic deterrence analytic capabilities: an assessment of tools, methods, and approaches for the 21st century security environment - National Research Council; Division on Engineering and Physical Sciences; Air Force Studies Board; Committee on U.S. Air Force Strategic Deterrence Military Capabilities in the 21st Century Security Environment (National Academies Press, 2015)
"Since the early 1960s, the U.S. strategic nuclear posture has been composed of a triad of nuclear-certified long-range bombers, intercontinental ballistic missiles, and submarine-launched ballistic missiles. Since the early 1970s, U.S. nuclear forces have been subject to strategic arms control agreements. The large numbers and diversified nature of the U.S. nonstrategic (tactical) nuclear forces, which cannot be ignored as part of the overall nuclear deterrent, have decreased substantially since the Cold War. While there is domestic consensus today on the need to maintain an effective deterrent, there is no consensus on precisely what that requires, especially in a changing geopolitical environment and with continued reductions in nuclear arms. This places a premium on having the best possible analytic tools, methods, and approaches for understanding how nuclear deterrence and assurance work, how they might fail, and how failure can be